Civil Liability of Influencers in Endorsement Contracts - Baskara, Septian Adhy; Akib, Ma'ruf; Umar, Wahyudi (PAMALI: Pattimura Magister Law Review, 2026)
Introduction: The rapid expansion of digital technology has transformed marketing practices and created a contractual ecosystem involving influencers as key promotional actors. This shift has generated distinctive legal issues concerning contract formation, consumer protection, and electronic information governance.Purposes of the Research: Examining the civil liability of influencers in endorsement contracts and analyzing the legal position of influencers in Indonesia's digital contractual ecosystem.Methods of the Research: This study employs a normative legal research method using statute, conceptual, and analytical approaches by examining provisions within the Civil Code, the Electronic Information and Transactions Law, and the Consumer Protection Law.Results Main Findings of the Research: The findings demonstrate that influencer liability in endorsement agreements is multilayered, covering both contractual (wanprestasi) and tort-based (onrechtmatige daad) responsibilities. The study also reveals the emergence of a digital-era duty of care requiring influencers to verify product legality and ensure truthful promotional content. This contributes to a modern reconstruction of contract doctrine in Indonesia’s digital economy.